Outcomes of temporomandibular joint disorders treatment after a survey in the population of Uttarakhand, Part I: An epidemiological study - Ashi Chug; Sagrika Shukla; Sumit Bhatt; kratika Soni (Elsevier, 2020)
Aim: To observe the prevalence of signs and symptoms of Temporomandibular joint disorders in patients visiting outpatient department, AIIMS Rishikesh. Method and material: The survey was conducted in a total of 960 patients, who visited outpatient Department (OPD), dept of Dentistry, AIIMS Rishikesh and were asked to fill a questionnaire based on Fonseca questionnaire for TMD in accordance to the inclusion and exclusion criteria. Results: Out of 960 patients, 449 had no TMD, 322 patients had mild TMD, 123 moderate and severe TMD was seen in 54 patients. Also, male dominance for TMD was seen in all the groups. There was no age predilection; however most of the patients with severe TMD fell between 16 and 60 years of age. Conclusion: TMD is a common problem occurring in all age groups, there was a male dominance seen in the epidemiological study.